2014
DOI: 10.1001/jamaophthalmol.2013.6326
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional Associations of Medication and Supplement Use With Retinal Vascular Diameter in the Beaver Dam Eye Study

Abstract: IMPORTANCE Retinal vessel diameters are being measured to examine their relationship with ocular and systemic disease and, in some studies, to calculate the risk of disease. Important factors that directly affect retinal vessel diameters, such as medication use, should be considered when estimating these associations.OBJECTIVE To quantify the association between selected medications and supplements and retinal vessel diameters. DESIGN, SETTING, AND PARTICIPANTS In a prospective cohort investigation, 4926 parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…Similarly, arteriolar dilation has been demonstrated in persons treated with statins (hydroxymethylglutaryl‐CoA reductase inhibitors) . These observations are consistent with data from the BMES where anti‐hypertensive use, particularly calcium channel blockers were associated with wider arterioles . The use of angiotensin‐converting enzyme inhibitors, thiazide diuretics and lipid‐lowering therapies has also demonstrated cross‐sectional associations with wider arterioles .…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Similarly, arteriolar dilation has been demonstrated in persons treated with statins (hydroxymethylglutaryl‐CoA reductase inhibitors) . These observations are consistent with data from the BMES where anti‐hypertensive use, particularly calcium channel blockers were associated with wider arterioles . The use of angiotensin‐converting enzyme inhibitors, thiazide diuretics and lipid‐lowering therapies has also demonstrated cross‐sectional associations with wider arterioles .…”
Section: Discussionsupporting
confidence: 79%
“…They found that the association between arteriolar narrowing and POAG was similar whether or not the subject was receiving treatment. Analysis of the BDES cohort showed that topical ocular hypotensives, particularly beta‐blockers and prostaglandin analogues were associated with narrowed arterioles and venules even though this population did not show link between glaucoma and narrowed vascular calibre . In clinic‐based studies, consistent effects of glaucoma therapy on vessel width have not been demonstrated.…”
Section: Glaucomatous and Non‐glaucomatous Optic Neuropathiesmentioning
confidence: 94%
See 1 more Smart Citation
“…In addition, the combined use of aspirin and antihypertensive agents was found to be related to wider retinal arteriolar diameter by the Blue Mountains Eye Study. 56 Howard et al 57 also found an effect of systemic medications on RVD. Because most of the subjects with systemic hypertension had been on medications in this study, it could have affected our results.…”
Section: Discussionmentioning
confidence: 94%
“…On the other hand, all subjects in the control group had no history of cardiac or pulmonary disorders that might have affected vascular diameter. Among some medications including calcium channel blockers, prostaglandin analogs, β-blockers, and oral corticosteroids, which might have influenced vascular diameter, 18 beraprost sodium, a prostaglandin analog, was taken by one patient in the preterm group. In the control group, no one had a history of any drug associated with vessel width.…”
Section: Clinical and Demographic Characteristicsmentioning
confidence: 99%